2007
DOI: 10.1161/circulationaha.106.666388
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Heart Rate Increase at Onset of Exercise Testing

Abstract: Background-The initial response of heart rate to dynamic exercise has been proposed as having prognostic value in limited studies that have used modalities other than the treadmill. Our aim was to evaluate the prognostic value of early heart rate parameters in patients referred for routine clinical treadmill testing. Methods and Results-The heart rate rise at the onset of exercise was measured in 1959 patients referred for clinical treadmill testing at the Palo Alto (Calif) Veterans Affairs Medical Center from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 21 publications
7
51
1
1
Order By: Relevance
“…The interpretation of this positive association shows that individuals with higher ΔHR tend to have a higher CVA as measured by CVI. Within this perspective, our findings corroborated, at least in part, those described by Leeper et al 14 , who recently demonstrated a better prognosis in individuals with ΔHR ≥12 bpm undergoing symptom-limited treadmill ET. The modest association found in our study may be explained by these authors' argument that the HR response in the 1st minute of exercise may reflect not only exercise-induced vagal withdrawal, but also the magnitude of the adrenergic response to exercise.…”
Section: Discussionsupporting
confidence: 92%
“…The interpretation of this positive association shows that individuals with higher ΔHR tend to have a higher CVA as measured by CVI. Within this perspective, our findings corroborated, at least in part, those described by Leeper et al 14 , who recently demonstrated a better prognosis in individuals with ΔHR ≥12 bpm undergoing symptom-limited treadmill ET. The modest association found in our study may be explained by these authors' argument that the HR response in the 1st minute of exercise may reflect not only exercise-induced vagal withdrawal, but also the magnitude of the adrenergic response to exercise.…”
Section: Discussionsupporting
confidence: 92%
“…18 The balance between parasympathetic and sympathetic activity is considered to be involved in both the initiation and the maintenance of AF. 19 The present main results-an increased AF risk associated with low HR at moderate exercise in healthy men-might suggest involvement of an inappropriate HR response to exercise with prolonged parasympathetic activation.…”
Section: The Autonomic Nervous Systemmentioning
confidence: 99%
“…Supporting this notion, indirect measures of cardiac parasympathetic dysfunction such as elevated resting heart rate, delayed heart rate recovery after exercise and attenuated heart rate increase during exercise have all been shown to be independent predictors for adverse cardiovascular outcome (1)(2)(3). Abnormalities in these parameters (4) have been shown in diverse study populations to be associated with sudden cardiac death (1,5) as well as all-cause mortality (2,3,6,7), but clinically validated biomarkers to assess the parasympathetic system are not yet available. Of note, the parasympathetic neurotransmitter, acetylcholine (ACh), is extremely labile and difficult to use for clinical measurements (8).…”
Section: Introductionmentioning
confidence: 99%